2018
DOI: 10.1080/08870446.2017.1423313
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative interview study of people living with well-controlled Type 1 diabetes

Abstract: Based on the experiences of people with well-controlled Type 1 diabetes, interventions for people with this condition should encourage acceptance of the diagnosis and increasing confidence to experiment with behaviours (trial and error) to encourage 'mastery' of self-management. The research collaboration described here is an example of best practice for future researchers wanting to actively engage PP partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 22 publications
3
13
0
Order By: Relevance
“…The participants' own systematic and accurate diabetes management methods were embodied in their bodies. This finding is consistent with the results of previous studies showing that the management of T1D requires changes in daily living (Whittemore, Jaser, Guo, & Grey, 2010) and that optimal methods of management align with the characteristics of individuals' daily lives (Smith et al, 2018). The area of diabetes care most emphasized by the participants was diet; similarly, a previous study reported that among 380 middle-aged persons with T1D, 8-9% selected insulin administration, 34% selected exercise and 55-56% selected diet as a major diabetes care area (Ozcan et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The participants' own systematic and accurate diabetes management methods were embodied in their bodies. This finding is consistent with the results of previous studies showing that the management of T1D requires changes in daily living (Whittemore, Jaser, Guo, & Grey, 2010) and that optimal methods of management align with the characteristics of individuals' daily lives (Smith et al, 2018). The area of diabetes care most emphasized by the participants was diet; similarly, a previous study reported that among 380 middle-aged persons with T1D, 8-9% selected insulin administration, 34% selected exercise and 55-56% selected diet as a major diabetes care area (Ozcan et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…In chronic disease patients' health care, the body and the mind are inseparable, intertwined in an organic relationship (Benner & Wrubel, 1989). Additionally, Smith et al (2018) explain that a balance between the body and the mind is a balance between the faith and the self-confidence achieved by managing daily activities such as diet therapy, exercise, and insulin administration. However, the findings of the present study show that although the scope of the participants' bodily activity was limited, their mindset was not limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because it was not feasible to perform a community-based face-to-face survey during this period, we conducted a telephone-based qualitative interview study in young adults with T1DM. Similar qualitative interview studies have been used in the past to assess the experiences, perceptions, behaviors and psychosocial aspects of people living with diabetes mellitus [ [15] , [16] , [17] , [18] , [19] , [20] , [21] ]. Although telephone-based qualitative interview has generally been considered inferior to in-person interviews [ 22 ], using telephone for qualitative interviews carries with it the logistic and practical advantages of improved access to geographically dispersed interviewees, reduced costs and increased interviewer safety [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Keeping blood sugar at normal levels in patients with diabetes can reduce the occurrence of complications such as cardiovascular disease, diabetic nephropathy, and sexual dysfunction. 18 25 …”
Section: Introductionmentioning
confidence: 99%